Preserving Perak’s cave art painting heritage in 360-degree immersion: Gua Tambun, Ipoh / Mohd Fairuz Ali ... [et al.] - Ali, Mohd Fairuz; Perng Jeu, Ng; Hwei Teeng, Chong; Kin Meng, Cheng (2024)
Exploring Tambun Cave's rock art in Perak, Malaysia, reveals a wealth of cultural heritage that necessitates proactive conservation efforts. This research focuses on implementing an interactive 360-degree panoramic view via a website platform, using Insta360 Pro cameras to capture the cave's intricate artworks. Methodologically, the process entails meticulously documenting the cave's interior with Insta360 Pro cameras, ensuring complete coverage of the rock art. These panoramic images are then stitched together and integrated into a website platform, allowing users to explore virtual environments. Drawing on collaborations with a renowned expert in rock art archaeology and Ventrex Outdoor Recreation, the study gains valuable insights into the artworks' cultural significance and interpretation, as well as practical considerations for immersive experiences in outdoor environments. By combining innovative technology with expert consultation, this study aims to enhance public engagement with Tambun Cave's rock art, fostering greater appreciation and support for its preservation.